Uniform range of core-making machines for production of sand cores with hardening in heated rigging - B. V. Kurakevich; A. P. Melnikov; G. I. Pasjuk; L. R. Sysoeva (Литьë и металлургия, 2001)
Structure peculiarities of the uniform range of core making machines for production of sand cores with hardening in heated rigging are considered and their technical characteristics are given.